(untitled) (ETIMA, 2021)
Abstract Smart metering is debated issue currently. It is a consequence of the introduction of this technology into practice, a many of pilot operations and the effort find the optimum technology for each area. The aim of the paper is a system for testing of selected functionalities of smart meters. In particular, the ability to evaluate the power quality parameters such as waveform distortion, detection of maximum and minimum values and other parameters defined in the standard STN EN 50160. Described system is under development and testing, so some functionality will put the finishing touches according to current requirements. Key words Smart meter, measuring, harmonics, testing